Introducing Care Ethics into Humanitarianism; Comment on "A Crisis of Humanitarianism: Refugees at the Gates of Europe" - Hara Kouki (Kerman University of Medical Sciences, 2021)
Since 2015, the so-called refugee crisis has transformed 'humanitarianism' into a word devoid of meaning or value for European politics. By now, we all know there are numerous migrant populations in Europe living under inhuman conditions and denied their inalienable human rights; still, it seems futile to argue that equal value should be attached to all lives. Introducing care ethics into relief work calls to reflect upon humanitarianism differently, as a relationship between local communities, Non-Governmental Organization (NGO) workers and refugees that is embedded in space and time and might be allowed to have a future.